Density driven currents in the Barents Sea calculated by a numerical model - Dag Slagstad; Kjell Støle-Hansen; Harald Loeng (Modeling, Identification and Control, 1990)
A baroclinic, 3-D model is described. It is adapted to a Barents Sea situation in order to simulate the currents in this area. The model is of a so-called level type which contains fixed, but permeable levels. It also includes thermodynamics which allow freezing and melting of ice. Using density data obtained during the autumn of 1988, a current pattern, driven by density and bottom topography is simulated. No wind is applied. The simulated current pattern gives an overall picture which is similar to what is observed through the few measurements that are available. Good agreements with the observations is found on the Svalbard bank, Tromsøflaket and along the Novaya Zemlya Coast. In the Bear Island/Hopen depth the model predicts a large eddy which has not been observed. Several smaller, topographical steared eddies are seen in the eastern part of the model area.